ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA UNIVERSITAS LAMPUNG DALAM MENGGUNAKAN APLIKASI PAYLATER - Muhammad Arif; Tiara Nirmala (Yayasan Education and Social Center, 2026)
The purpose of this study is to examine the variables that affect University of Lampung students' decisions to use PayLater services. With 397 respondents chosen using Slovin's algorithm, the study employs a quantitative approach with an associative strategy. Questionnaires were used to gather data, and a Likert scale was used for descriptive analysis. Student income, pricing perception, financial management practices, consumption, risk, and security are among the variables examined. According to the study's findings, the majority of the variables fall into the high group, indicating that students have a respectable degree of financial literacy, consumption, and confidence in PayLater services. With only 33% of respondents using PayLater, the choice to use the service is still regarded as low to medium. This suggests that students still think about financial concerns and their capacity to pay even when PayLater provides ease and flexibility. While financial management and risk perception discourage excessive use, income and price perception typically encourage usage. Increasing trust is also influenced by security perception. All things considered, PayLater turns into a useful payment option, but it necessitates prudent money management.